Ethnic differences in the frequency of prostate cancer susceptibility alleles at SRD5A2 and CYP3A4 - Zeigler-Johnson, C.M.; Walker, A.H.; Mancke, B.; Spangler, E.; Jalloh, M.; McBride, S.; Deitz, A.; Malkowicz, S.B.; Ofori-Adjei, D.; Gueye, S.M.; Rebbeck, T.R. (Human Heredity, 2002)
Objectives: Ethnic differences in prostate cancer incidence are well documented, with African-Americans having among the highest rates in the world. Ethnic differences in genotypes for genes associated with androgen metabolism including SRD5A2 and CYP3A4 also may exist. The aim of this study was to evaluate differences in these genotypes by ethnicity. Methods: We studied cancer-free controls representative of four groups: 147 African Americans, 410 Caucasian-Americans, 129 Ghanaians, and 178 Senegalese. PCR-based genotype analysis was undertaken to identify two alleles (V89L, A49T) at SRD5A2 and *1B allele at CYP3A4. Results: Differences were observed for V89L (variant frequency of 30% in Caucasians, 27% in African Americans, 19% in Ghanaians, and 18% in Senegalese, p =0.002) and were observed for CYP3A4*1B (variant frequencies of 8% in Caucasians, 59% in African Americans, 81% in Ghanaians, and 78% in Senegalese, p =0.0001). Pooled data combining the present data and previously published data from from Asian, Hispanic, and Arab cancer-free controls showed significant ethnic differences for SRD5A2 and CYP3A4 polymorphisms. Overall, Asians were least likely to have alleles associated with increased prostate cancer risk, while Africans were most likely to have those alleles. Conclusions: These results suggest that ethnicity-specific differences in genotype frequencies exist for SRD5A2 and CYP3A4. Africans and African-Americans have the highest frequency of those alleles that have previously been associated with increased prostate cancer risk. Future studies should address whether allele frequency differences in part explain differences in prostate cancer incidence in these populations. Copyright © 2002 S. Karger AG, Basel.
Keywords: CYP3A4; Ethnicity; Genotypes; Prostate cancer; SRD5A2